Impact of Low Hemoglobin on Contrast-Induced Nephropathy After Percutaneous Coronary Intervention - Akhtaruzzaman, M; Choudhury, AK; Khalequzzaman, M; Barua, SK; Choudhury, TA; Hasem, S; Majumder, NK; Islam, AKM Monwarul; Chowdhury, S; Chowdhury, AHK (Cardiovascular Journal, 2012)
Background: Contrast-Induced Nephropathy (CIN) is an iatrogenic disorder, resulting from exposure to contrast media. The aim of this study was to assess whether anaemia is a predictor of contrast induced nephropathy after Percutaneous Coronary Intervention (PCI). Methods: This was a prospective observational study. A total of one hundred patients fulfilling the inclusion and exclusion criteria who underwent (PCI) Percutaneous Transluminal Coronary Angioplasty with stenting, were studied during the study period of two years from January 2008 to December 2009. Patients were divided into two groups : Group-I (n=50), patients with low hemoglobin (male <13-10gm/dl, female < 12-10 gm/dl) and Group-II (n=50), patients with normal hemoglobin (male ?13gm/dl, female ?12gm/dl). Non-ionic low-osmolar contrast agents was used in all patients.Volume of contrast medium (ml) was recorded. Adequate hydration given intravenously (ml). Prior to procedure serum creatinine, serum electrolytes and Creatinine clearance rate were measured within 24 hrs before PCI and on days 1,2,3 after PCI. If there is renal impairment (CIN) serum creatinine, serum electrolytes and Creatinine clearance rate were measured daily from the 4th day onward after PCI until recovery. Results: The mean serum creatinine level of low hemoglobin group and normal hemoglobin group were 0.9mg/dl and 1mg/dl respectively at base line. The low hemoglobin group experienced a considerable increase in serum creatinine up to 1.5mg/dl at day 3 compared to 1.3 mg/dl in normal hemoglobin group. When the most common definition of contrast induced nephropathy (as an increase in the serum creatinine concentration >0.5 mg/dl from baseline) was used the incidence of CIN was 26% in low hemoglobin group and 8% in the normal hemoglobin group. Conclusion: preprocedural low hemoglobin is an independent determinant of increased incidence of contrast induced nephropathy after percutaneous coronary intervention. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12226 Cardiovasc. j. 2012; 5(1): 30-36